The Effect of Problem Based Learning (PBL) Charged Science Literacy Toward Students’ Learning Competences at XI Grade of SMAN 1 Lubuk Alung - Sintia Elmanazifa; S. Syamsurizal (Universitas Negeri Padang, 2018)
This research based on the problem on SMAN 1 Lubuk Alung, those are inappropriate learning model choices and low of students’ learning competencies. An efforts could done to solve it was implementation of problem based learning model charged with science literacy toward the students’ learning competencies on the topic of excretion system at XI grade of SMAN 1 Lubuk Alung. This research aimed to know the effects of Problem Based Learning (PBL) charged with science literacy toward the students’ learning competencies at XI grade of SMAN 1 Lubuk Alung. The type of this research was experimental research and designed on Control Group Posttest Only. The populations of this research were all of the students at grade XI MIPA of SMAN 1 Lubuk Alung academic years 2017/2018 that consisted of seven classes. This research used purposive sampling technique to take the samples; those are XI MIPA 3 as experiment group and XI MIPA 2 as control group. The research’s instruments used were test for cognitive competence and observation sheets for affective and psychomotor competence. Hypothesis was tested by using T-test method.Based on the thesis result by using t-test, it can be concluded that on students’ cognitive competence tscore 4,15> table 1,67, on students’ affective competence tscore 5,07 > table 1,67, and on students’ psychomotor competence tscore 1,69 > table 1,67. It showed that hypothesis was accepted. So it can be concluded that the implementation of Problem Based Learning (PBL) charged science literacy model improved toward students’ learning competences at XI grade of SMAN 1 Lubuk Alung significantly with 0,05 degrees of truthiness.